Model of 2-Dimensional Layered Spatial Distribution of Suspended Load in Lake Tempe - Harsono, Eko (Oseanologi dan Limnologi di Indonesia, 2016)
Accumulation of sediment in Lake Tempe deriving from Bila, Sidenreng, and Batu-batu Rivers in the region of Walannae River will be dredged during barrage operation, but until now the location of sediment accumulation in the lake is still unknown. This study developed a model of 2-dimensional layered spatial distribution of suspended materials in Lake Tempe to determine the extent of sedimentation in the lake from suspended material inputs, so the location of sediment dredging can be determined appropriately. Model was calibrated using the observation data of TSS concentrations at 15 points in Lake Tempe at water level of 5 m which took place in March 2014. The result showed that the model was in accordance with the observed data. Based on the simulation of range setting of effluent discharge, it is known that if the range setting of effluent discharge is narrowed, the deposition of suspended loads in the lake becomes higher, so the TSS that comes out of the lake will be less. Based on the model simulation and simulation of suspended load reduction of the influent for each zone, the accumulation of sediment in Lake Tempe happens around the deepest area between Zone I and Zone III, and the factor affecting the distribution of TSS in the lake is the suspended loads of the influent from Bila River and the effluent discharge.